2019
DOI: 10.3390/ijms20215272
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Gene Expression in Adipose Tissue of Obese Individuals is Regulated by miRNA and Correlates with the Pro-Inflammatory Cytokine Level

Abstract: Background: Given the role that vitamin D (VD) plays in the regulation of the inflammatory activity of adipocytes, we aimed to assess whether obesity changes the expression of VD-related genes in adipose tissue and, if so, to investigate whether this phenomenon depends on microRNA interference and how it may influence the local inflammatory milieu. Methods: The expression of genes encoding VD 1α-hydroxylase (CYP27B1), 24-hydroxylase (CYP24A1) and receptor (VDR), selected interleukins and microRNAs was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 36 publications
0
28
0
3
Order By: Relevance
“…Our finding that the gene for the Vitamin D receptor was the most up-regulated gene in ciliated cells in response to MCH was at first surprising to us, but upon further examination and when placed in the context of the complete transcriptome response in ciliated adipocytes, it becomes clearer. Vitamin D regulates the inflammatory response in adipocytes 36 , and modulation of receptor availability by MCH could be a means by which the inflammatory response is controlled. Expression of vdr is elevated in early adipogenesis and it is hypothesized that 1,25(OH)2D3 could exert an anti-adipogenic effect via Wnt/b-catenin.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding that the gene for the Vitamin D receptor was the most up-regulated gene in ciliated cells in response to MCH was at first surprising to us, but upon further examination and when placed in the context of the complete transcriptome response in ciliated adipocytes, it becomes clearer. Vitamin D regulates the inflammatory response in adipocytes 36 , and modulation of receptor availability by MCH could be a means by which the inflammatory response is controlled. Expression of vdr is elevated in early adipogenesis and it is hypothesized that 1,25(OH)2D3 could exert an anti-adipogenic effect via Wnt/b-catenin.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover the above mechanisms would not explain why the differential release is only observed for 1,25(OH) 2 D 3 and not for 25(OH)D 3. Vitamin D 1,25(OH) 2 D 3 is a ligand for vitamin D receptor (VDR), and it has been shown that vitamin D receptor (VDR) expression is increased in SAT of individuals with obesity (Jonas et al, 2019). From the latter, it could be speculated that vitamin D 1,25(OH) 2 D 3 binds to a higher extent to VDR within SAT in individuals with obesity, resulting in less spillover of vitamin D 1,25(OH) 2 D 3 in the circulation in obese individuals but not in lean, which still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Регуляторные сети микроРНК особенно важны для сигнальных молекул, к которым относится витамин D, оказывающих плейотропное действие на различные органы и ткани организма. В недавних исследованиях показана роль 1,25(OH)D в эпигенетической регуляции генов, особенно в качестве модулятора функции микроРНК [36].…”
Section: эпигенетические механизмы регуляции рецептора ви тамина Dunclassified